2013
DOI: 10.1152/ajpregu.00200.2013
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol supplementation improves white adipose tissue function in a depot-specific manner in Zucker diabetic fatty rats

Abstract: Resveratrol (RSV) is a polyphenolic compound suggested to have anti-diabetic properties. Surprisingly, little is known regarding the effects of RSV supplementation on adipose tissue (AT) metabolism in vivo. The purpose of this study was to assess the effects of RSV on mitochondrial content and respiration, glyceroneogenesis (GNG), and adiponectin secretion in adipose tissue from Zucker diabetic fatty (ZDF) rats. Five-week-old ZDF rats were fed a chow diet with (ZDF RSV) or without (ZDF chow) RSV (200 mg/kg bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 56 publications
2
55
1
Order By: Relevance
“…Beaudoin et al (47) demonstrated that 6 weeks of high-dose resveratrol administration (200 mg/kg daily) increases the adiponectin concentration and its release from adipose tissue in Zucker rats. Gómez-Zorita et al (48) demonstrated similar results to Beaudoin et al (47) following 6 weeks of 15 mg/kg resveratrol administration daily. By contrast, Palsamy and Subramanian (49) did not observe a significant increase of plasma adiponectin levels following 30 days of low-dose resveratrol treatment (5 mg/kg) in a healthy population of Wistar rats.…”
Section: Discussionsupporting
confidence: 55%
“…Beaudoin et al (47) demonstrated that 6 weeks of high-dose resveratrol administration (200 mg/kg daily) increases the adiponectin concentration and its release from adipose tissue in Zucker rats. Gómez-Zorita et al (48) demonstrated similar results to Beaudoin et al (47) following 6 weeks of 15 mg/kg resveratrol administration daily. By contrast, Palsamy and Subramanian (49) did not observe a significant increase of plasma adiponectin levels following 30 days of low-dose resveratrol treatment (5 mg/kg) in a healthy population of Wistar rats.…”
Section: Discussionsupporting
confidence: 55%
“…It is possible that in our experimental model, resveratrol was able to change the molecular profile of these metabolic pathways resulting in lower fat deposition and improvement of obesity. Contrarily, in a recent study using Zucker diabetic fatty (ZDF) rats, it was demonstrated that resveratrol treatment (200 mg/Kg BW/day) did not affect adipose tissue mass or body weight, but resveratrol induced marked changes in the adipose tissue metabolism, such as increased mitochondrial biogenesis with increase in peroxisome proliferator-activated receptor coactivator-1 (PGC-1α) and also increased adiponectin synthesis in a depot-specific manner [27]. Another possible mechanism associated with reduced fat mass induced by resveratrol would be through the increase in fatty acid oxidation in skeletal muscle and liver, increasing energy expenditure and possibly increasing the demand of lipolysis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Adipocyte cell sizing and immunohistochemistry Adipose tissue was fixed, embedded and stained as previously reported [22]. Macrophage infiltration was assessed by F4/80 (1:100, AbD Serotec, BioRad, Hercules, CA, USA) staining visualised using the Vectastain ABC kit (Vector Laboratories, Burlingame, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…High-resolution respirometry Mitochondrial respiration was determined in permeabilised WAT in an Oxygraph high-resolution respirometer chamber at 37°C (Oroboros Instruments, Innsbruck, Austria) as previously described [22,23]. ADP-stimulated respiration (state 3) was measured in the presence of pyruvate (5 mmol/l), malate (5 mmol/l) and ADP (5 mmol/l) or malate (5 mmol/l), L-carnitine (5 mmol/l), palmitoyl-CoA (50 μmol/l) and ADP (5 mmol/l).…”
Section: Methodsmentioning
confidence: 99%